Position-specific biomarker responses to match vs. VAMEVAL test modalities in elite female soccer players: a comparative analysis study - Manel Slimani; Hatem Ghouili; Wissem Dhahbi; Zouhaier Farhani; Mohamed Ben Aissa; Marouen Souaifi; Noomen Guelmami; Ismail Dergaa; Lamia Ben Ezzeddine (Cogent Social Sciences)
To examine the effects of exercise type (competitive match vs. VAMEVAL test) and playing position on biomarker responses in elite female soccer players, twenty-one athletes (seven each: defenders, midfielders, attackers) participated in this cohort-based study. Blood samples were collected before and 3 minutes after both a competitive match and VAMEVAL test, analyzing 19 biomarkers including metabolic, lipid, protein, inflammatory, and immune parameters. Significant effects (p<0.001–0.004; ƞ2p:0.36–0.59[large]) were observed in biomarkers reflecting energy metabolism (glucose), protein turnover (albumin), inflammation (tumor necrosis factor and C-reactive protein), and lipid profile (apolipoprotein-B) across conditions. Match play increased glucose levels in defenders and midfielders (p<0.003) and inflammatory markers (p<0.014) compared to VAMEVAL. Position-specific responses emerged: attackers showed higher urea (p=0.032) while midfielders displayed unique lipid profiles (p=0.033) post-match. These findings, supported by significant interactions (p<0.05), emphasize the importance of considering both exercise modality and playing position when developing personalized training and recovery strategies in female soccer, highlighting the distinct metabolic demands across positions and exercise conditions.